2013
DOI: 10.1038/srep03308
|View full text |Cite
|
Sign up to set email alerts
|

hERG1 channels modulate integrin signaling to trigger angiogenesis and tumor progression in colorectal cancer

Abstract: Angiogenesis is a potential target for cancer therapy. We identified a novel signaling pathway that sustains angiogenesis and progression in colorectal cancer (CRC). This pathway is triggered by β1 integrin-mediated adhesion and leads to VEGF-A secretion. The effect is modulated by the human ether-à-go-go related gene 1 (hERG1) K+ channel. hERG1 recruits and activates PI3K and Akt. This in turn increases the Hypoxia Inducible Factor (HIF)-dependent transcription of VEGF-A and other tumour progression genes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 61 publications
3
106
0
Order By: Relevance
“…The regulation of VEGF-A secretion occurs exclusively in gastric cancer cells expressing hERG1 at high levels, a fact proven by both pharmacologic and biomolecular hERG1 inhibition. Moreover, such regulation can be traced back to a signaling mechanism triggered by hERG1 and ending into the regulation of HIF transcriptional activity (22). Interestingly, it takes place in normoxic condition when HIF is usually rapidly degraded (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of VEGF-A secretion occurs exclusively in gastric cancer cells expressing hERG1 at high levels, a fact proven by both pharmacologic and biomolecular hERG1 inhibition. Moreover, such regulation can be traced back to a signaling mechanism triggered by hERG1 and ending into the regulation of HIF transcriptional activity (22). Interestingly, it takes place in normoxic condition when HIF is usually rapidly degraded (21).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A expression is mainly controlled by the activity of the transcription factor HIF, whose "a" subunit is under control of either O 2 tension or intracellular signaling pathways (21). We recently reported that VEGF-A transcription in colorectal cancer cells was controlled by a peculiar signaling pathway triggered by the hERG1/b1 integrin complex, centered on Akt and converging on the regulation of the 2 HIF-a transcripts: HIF-1a and HIF-2a (22). Hence, we tested whether the same pathway was controlled by hERG1 in gastric cancer cells.…”
Section: Herg1 Channels Drive Vegf-a Secretion In Gastric Cancermentioning
confidence: 99%
“…FDM promotes hERG current density through a rapid Sig1R-dependent recruitment of channels at the surface In leukemic and colorectal cancer cells, hERG current can be stimulated by b1 subunit of integrin heterodimers, which are themselves activated by ECM components, such as fibronectin (7,9,10). To assess whether Sig1R participates to the dynamic regulation of hERG channel in response to ECM stimulation, patch-clamp experiments were performed.…”
Section: Sig1r Is Overexpressed In Human Cancersmentioning
confidence: 99%
“…For example, KCNH2 (human ether-a-go-go-related gene, hERG), a voltage-dependent K þ channel mainly involved in cardiac activity (6), has been characterized as a biomarker of many solid tumors (colorectal cancer, glioblastoma, head and neck cancers; refs. 7,8) and acute or chronic leukemias [acute myelogenous leukemia (AML), acute lymphoblastic leukemia (ALL), and chronic myelogenous leukemia (CML), respectively; refs. 9,10].…”
Section: Introductionmentioning
confidence: 99%
“…29 In Fig. 1B The expression of VEGF-A in primary GC was studied only by IHC, due to the broad expression of VEGF-A in stromal cells of the gastric submucosa.…”
Section: Characteristics Of Study Cohortmentioning
confidence: 99%